El Imperio de Brasil, los estados platinos en el prólogo de la guerra de 1865 - Johny Santana de Araújo (Caravelle)
This article discusses about the diplomatic actions and military operations of the Brazilian Empire towards Uruguay during the period previous to war against Paraguay in 1865. It is considered that such operations and the resulting war would be the product of a great quarrel for political influence and sovereignty during the context of the consolidation process of these South American national states, as well as the result of their interests’ expansion in La Plata region.